دراست اعتراضاث ابن هشام الأنصاري على المفسرين سورة البقرة – أنموذجا- - بن عمارة, الزهرة (University of Eloued-جامعة الوادي, 2016)
تعنى ىذه المذكرة بموضوع ذي أىمية بالغة وجدير بالبحث ألا وىو :د ا رسة اعت ا رضات ابن ىشام الأنصاري على المفسرين – سورة البقرة أنموذجا- تضمنت الد ا رسة في الفصل الأول: - ترجمة موجزة لابن ىشام )الحالة السياسية ، الحياة الفكرية والدينية الحياة الشخصية و العلمية لابن ىشام ( ؛ إذ ساىم استق ا رر عيد المماليك وازدىاره في نشوء طيب لابن ىشام ونبوغو بين العلماء . - وفي الفصل الثاني بيان ماىية الاعت ا رضات ومنيجو فييا ، وأبرز المفسرين الذين ورد الاعت ا رض علييم - وقد اشتمل الفصل الثالث على الجزء التطبيقي وبيان الاعت ا رضات على المفسرين التي حوتيا سورة البقرة .ثم الخاتمة التي حوت أىم النتائج والتوصياتThis note dealing with the subject of enormous importance and worthy of research, namely: Study objections Ibn Hisham al-Ansari on the commentators - Sura Onmozja- study included in the first chapter: - A brief translation of Ibn Hisham (political, intellectual and religious life Personal life and scientific Ibn Hisham); the stability and prosperity of the Mamluk era contributed to the emergence of good Ibn Hisham and his genius among scientists. - In the second chapter indicate what objections and approach them, and the most prominent commentators who have stated their objection - Chapter III has been included on the application and the statement of objections to the commentators that Hutea Sura Then whale conclusion that the most important findings and recommendations
مذكرة